Evaluating the Dynamic Interactions of Remittances, FDI, and Trade Balance on Sri Lanka’s GDP: Evidence from Co-Integration Analysis - Koswatta, A.; Lasanthi, M.; Vitharana, Y.; Perera, S.; Morais, N. (Department of Economics, University of Colombo, Sri Lanka., 2025)
Trade balance, remittances, interest rates, Foreign Direct Investment (FDI), and external debt are key macroeconomic components that drive economic growth in a country. This study analyzes the interconnection among these elements and the manner in which they influence Sri Lanka's economic growth. With the usage of structured country data and advanced econometric techniques, the analysis suggests that these relationships are more complex than they appear. According to the results, both trade balance and FDI spur growth. However, that growth is subjected to the standard of the institutions and the status of openness of the economy. Although remittances are important for the welfare of the households, there is a progressive decline in growth returns at higher levels of dependency, hence emphasizing the fact that these funds need to be invested in a more productive manner. Interest rates increase investment when the economy is stable. However, they increase volatility when debt levels are high. While external debt can fuel growth, if not managed judiciously it can lead to excessive economic burdens which hinder sustainability of growth in the log-run. These findings refer to further importance in deriving policy initiatives that execute fiscal and monetary policies and trade policies in a harmonized way to increase the growth potential and strengthen the resilience of the Sri Lankan economy.
Keywords: External Debt; FDI; Interest rates; Remittances; Structural Vulnerabilities; Trade Balance